Deficits in reaching movements under visual interference as a novel diagnostic marker for mild cognitive impairment - Ciro Rosario Ilardi; Giovanni Federico; Marco La Marra; Raffaella Amato; Alessandro Iavarone; Andrea Soricelli; Gabriella Santangelo; Sergio Chieffi (Scientific Reports)
Abstract Patients with Mild Cognitive Impairment (MCI) may exhibit poorer performance in visuomotor tasks than healthy individuals, particularly under conditions with high cognitive load. Few studies have examined reaching movements in MCI and did so without assessing susceptibility to distractor interference. This proof-of-concept study analyzed the kinematics of visually guided reaching movements towards a target dot placed along the participants’ midsagittal/reaching axis. Movements were performed with and without a visual distractor (flanker) at various distances from the reaching axis. Participants were instructed to avoid “touching” the flanker during movement execution. The whole sample included 11 patients with MCI due to Alzheimer’s disease, 10 healthy older adults, and 12 healthy young adults, all right-handed. Patients with MCI performed reaching movements whose trajectories deviated significantly away from the flanker, especially when it was 1 mm away, with less consistent trajectories than controls. Also, our results suggest that trajectory curvature may discriminate between patients with MCI and healthy older adults. The analysis of reaching movements under conditions of visual interference may enhance the diagnosis of MCI, underscoring the need for multidimensional assessments incorporating both cognitive and motor domains.